THE IMPORTANCE OF TEACHING STUDENTS USING GEOGEBRA IN TEACHING GEOMETRY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the importance and advantages of using GeoGebra in teaching geometry. GeoGebra serves to increase students' interest in geometry, visually reinforce concepts and develop logical thinking skills by creating an interactive environment. The article also gives recommendations on how to use the program effectively.